(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Technology assessment (TA) emerged over 50 years ago as a scientific approach for analyzing and evaluating the consequences of technology. The main reason for this was the increasing awareness of negative consequences of technology. Parliamentary TA originated in the US Congress. Since the 1980s, it has been established in many European parliaments. This article describes the work of the Office of Technology Assessment at the German Bundestag. It reflects on the experiences gained in over 30 years of existence. A clear distinction between scientific and political mandates has proven to be central to the well-functioning of parliamentary policy advice.